2011
DOI: 10.1159/000332581
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Cardiac Function following Transplantation of Human Umbilical Cord Matrix-Derived Mesenchymal Cells

Abstract: Objectives: Human umbilical cord mesenchymal cells (hUCM) can be easily obtained and processed in a laboratory. These cells may be considered as a suitable source in the repair of heart failure diseases. We, therefore, examined whether these cells may contribute to heart regeneration following an acute experimental myocardial infarction (MI). Methods: MI-induced animals received 5 × 106 hUCM cells, 5 × 106 5-azacytidine-treated cells (dhUCM), or PBS alone, subepicardially. A group of anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…In this study, EF and FS, in MI groups decreased significantly compared to the intact group, five days post MI, which suggests that the treatment of the injured heart's function (dhUCM, VEGF and dhUCM+VEGF) didn't have any advantage at this point. Four weeks post MI, EF significantly increased in three treated animal groups, compared with the non-treated animal groups, in accordance with Latifpour's results [25]. Although increased EF was significantly higher in dhUCM+VEGF group compared with dhUCM only and VEGF only groups, the difference between the last two groups was trivial and negligible.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In this study, EF and FS, in MI groups decreased significantly compared to the intact group, five days post MI, which suggests that the treatment of the injured heart's function (dhUCM, VEGF and dhUCM+VEGF) didn't have any advantage at this point. Four weeks post MI, EF significantly increased in three treated animal groups, compared with the non-treated animal groups, in accordance with Latifpour's results [25]. Although increased EF was significantly higher in dhUCM+VEGF group compared with dhUCM only and VEGF only groups, the difference between the last two groups was trivial and negligible.…”
Section: Discussionsupporting
confidence: 86%
“…Many scientists have administered various stem cells directly to infarcted heart before a differentiation of those cells into cardiogenic in vitro [11,28,31]. Latipour et al have demonstrated that hUCM and dhUCMtransplantation in to infarcted myocardium improved cardiac function thirty days after MI [25]. Although cardiac microenvironment potentially introduced stem cells to cardiomyocyte differentiation, some surveys have revealed that less than 5% of cardiomyocytes are derived from stem cells in the recipient heart tissue [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 2, mice in the intravenous group (IV-u2w, IV-u1m) were injected intravenously with 1 × 10 6 hUCMSCs in 100 μL of PBS as described in previous studies (31)(32)(33). Mice in the IV-p2w and IV-p1m groups were injected with 100 μL of PBS alone.…”
Section: Hucmsc Transplantationmentioning
confidence: 99%
“…Based on their various advantages, the use of hUC-MSCs has yielded good results in the treatment of cardiovascular diseases (Wu et al, 2007;Latifpour et al, 2011). Although the treatment of MSCs has progressed in recent years, their effects of ischemia, hypoxia, invasion of inflammatory cells, and other factors in damaged zones can lead to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%